Amino acids shape the metabolic and immunologic landscape in the tumor immune microenvironment: from molecular mechanisms to therapeutic strategies - Ziyou Lin; Chang Chang; Shuyu Zhao; Lan Fang; Ping Wang (Cancer Biology & Medicine)
The tumor immune microenvironment (TIME) represents a complex battlefield where metabolic competition and immune evasion mechanisms converge to drive cancer progression. Amino acids, with their multifaceted biological roles, have emerged as pivotal regulators of tumor cell proliferation and immune cell functionality. The sensing mechanisms by which amino acids within the tumor microenvironment influence cellular growth, survival, and immune function are systematically explored in this review; the latest advances in understanding amino acid metabolism in tumor biology are also reviewed. In addition, the multifaceted roles of key amino acids in shaping the TIME with particular emphasis on tumor immunity and malignant growth were investigated. Finally, emerging therapeutic strategies targeting amino acid metabolism to reprogram the TIME are discussed, highlighting promising approaches, such as CAR-T cell therapy and engineered bacterial interventions. Through this comprehensive analysis, critical insights into future research directions and potential clinical translation of amino acid-targeted interventions are provided.